Graphitic carbon nitride polymers: promising catalysts or catalyst supports for heterogeneous oxidation and hydrogenation. Issue 2 (21st November 2014) - Gong, Yutong; Li, Mingming; Li, Haoran; Wang, Yong
Abstract : The review summarizes recent oxidation and hydrogenation strategies catalyzed by g-C3 N4 based systems. Abstract : Due to their industrial indispensability, heterogeneous catalytic oxidation and hydrogenation continue to be topics of great interest in both experimental and theoretical studies. Graphitic carbon nitride (g-C3 N4 ), due to its unique structure and thus excellent properties such as semiconductivity and nitrogen richness, is suitable to act as a metal-free catalyst or catalyst support for these two significant transformations. This critical review will summarize the recent significant advances achieved in the field of oxidation and hydrogenation realized by g-C3 N4 based catalytic systems. The review covers the practical applications and brief mechanistic discussions in three broad catalytic cases, catalytic oxidation under light irradiation, catalytic oxidation without light illumination, and catalytic hydrogenation with g-C3 N4 supporting metal nanoparticles. The state-of-the-art and future challenges of heterogeneous hydrogenation and oxidation by g-C3 N4 based systems are also discussed.